Peningkatan Kualitas Pendidikan Islam melalui Aspek Spiritual: Tinjauan Terhadap Praktek Pendidikan Spiritual - Giyarsi, Giyarsi (An-Nuha, 2023)
Education in today's generation faces serious problems related to spiritual crises and character traits that are very worrying. Spiritual and religious values are increasingly mired in Indonesian society in the search for moral values and wisdom, and this happens in everyday social life. Many Indonesians seem to face an empty personality, where values, vision, and heart are almost lost. Even more worrisome is that this condition is already affecting children. Therefore is very important to strengthen the quality of education through the spiritual aspect. This research is qualitative research aimed at determining the practice of spiritual strengthening of children to improve the quality of education at MDA Hidayatul Ummah North Bengkulu. The results showed that the method used in shaping and strengthening the spiritual aspects of students at MDA Hidayatul Ummah is the implementation and practice of shalawat wahidiyah and its teachings through mujahadah wahidiyah. By following the mujahadah wahidiyah with istiqamah and according to the guidance that has been set, students can cultivate spiritual values in their hearts to become individuals with strong beliefs, noble character, and the ability to think healthy and correct.